(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
This article aims to recognize environmental enterprises in San Luis. They are systematized according to various categories provided by the Environment Secretary of the province, and depending on their locations. The purpose of the study is to identify the experiences and obtain a series of significant considerations for future approaches to the topic, which allow promoting dialogues based on academic, popular and professional knowledge linked to socio-environmental sustainability.